EXPLORING THE INFLUENCE OF CONVERGENT COMMUNITIES ON LEARNERS’ ATTITUDES TOWARD DIVERGENT TRAITS - Belaid, Louiza (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The cultural context of speech communities represents people’s life experiences shaped by region, geography, ethnicity, language, and values; all these contribute to the construction of one’s identity. Our study explores the complex reciprocity between the socio-cultural environment and the learners’ identities. The cultural background of learners profoundly affects self-perception and identity construction. Simultaneously, identity construction has a reciprocal effect on interaction and involvement with cultural heritage. Hence, we investigate the impact of rural communities’ cultural repertoire on the personal and professional prospects of learners. To reach this end, third-year pupils from the High School of Sidi Housni, Tiaret, Algeria were selected using a non-probabilistic sampling. We collected data through a survey and an observation, employing both quantitative and qualitative approaches. The findings reveal that the cultural background influences learners’ perceptions of the world, besides their positive divergent attitudes towards gender roles. Furthermore, these valuable insights have important implications for cultivating a more inclusive and flexible learning setting. In a nutshell, divergent and convergent communities possess distinct qualities and resources that collectively foster a gradual transition toward embracing change.